Pengembangan Komik Cerita Rakyat Asal Usul Sungai Sorai Untuk Siswa Kelas V Sekolah Dasar - Suwitri, Muharramah; Kurniaman, Otang; Munjiatun, Munjiatun (Unversitas Katolik Santo Thomas, 2021)
This study aims to produce a folklore comic about the origin of the sungai sorai for fifth grade elementary school students and to determine the feasibility of the sungai sorai origin folklore comic for fifth grade elementary school students. This study uses the Research and Development (R&D) method or research and development using the Four-D model (Define, Design, Develop, Disseminate). Data collection techniques used are interviews, questionnaires and written tests. The feasibility of folklore comics was obtained from the results of validation, product trials and written tests. Validation is carried out by design experts, linguists and practitioners. The product trials conducted were limited to only 10 students. The written test used is in the form of objective questions to determine students' knowledge and understanding of folklore comics. The results showed that the validation of design experts obtained an assessment with a very valid category. In validation, linguists obtained an assessment with a very valid category. The next validation is practitioner validation with a very valid category. The product trial used is a limited product trial with the category of student response assessment which is very good. The student's written test in the form of objective questions about folklore comics received an assessment in the very good category. The results of this development research indicate that the folklore comic